INTEGRASI MATERI ENERGI ANGIN PADA MATERI USAHA, ENERGI, GETARAN HARMONIS, MOMENTUM DAN IMPULS TERHADAP HASIL BELAJAR FISIKA DALAM PEMBELAJARAN SYSTEMIC PROBLEM SOLVING - Selma Riyasni; Hamdi Rifai; Ahmad Fauzi (Universitas Negeri Padang, 2015)
The low student learning outcomes are caused by competence of problem solving is low. student can increase their competence of problem solving with solve the hot issue. The issues raised can be a problem and a solution of energy crisis in the form of wind energy. Presentation material can use worksheets that have integrated wind energy materials. This research aims to : 1 ) Investigate the influence of LKS integrated wind energy material to the learning outcomes Physics at XIth SMAN 6 Padang 2 ) Investigate the contribution of wind energy material integrated worksheets for learning outcomes physics class XI SMAN 6 Padang. Type of research is quasi-experimental study with randomize control group only design. The population of this study were all students of class XI MIA ( Mathematics and Natural Sciences ) SMAN 6 Padang listed in the Academic Year 2014 / 2015. Sampling was done by purposive sampling technique. The research data in the form of data learning outcomes of students competency of knowledge, attitudes and skills as well as the integrated value data LKS wind energy materials. Data were analyzed using two similarity test average at significance level 0.05, regression and correlation test on the competence of knowledge, attitudes and skills. Conclusion The study are integrated LKS influence of wind energy on the material work and energy , harmonious vibration, momentum and impulse to the study of students of class XI SMAN 6 Padang accepted at the 0,05 significance level. The amount of the contribution of LKS integrated wind energy strong, and the competence of skills is strong